La implementación del Lease Back y su incidencia en el desarrollo económico - financiero en la empresa Riego Nor SAC en la ciudad de Chepen 2014. - Saldaña Chicoma, Jaclyn Jajaira (2016)
The aim of the research was to determine the impact on economic and financial development in the company Riego Nor SAC retro implementation of leasing in the year 2014. The problem statement is formulated: How lease back implementation impacts in financial development - economic Company Riego Nor SAC Nor SAC? The research was explanatory correlational in the same sample. To carry out this research study has taken into account the economic and financial information of the company Riego Nor SAC S.A.C, shown in the statement of financial position and income statement as of December 31, 2013 and 2014. The results obtained in implementing the Retro Financial leasing is that it allows a fixed asset as a funding source so that does not lose the use said fixed assets; if this is sold and at the same time put in leasing, not losing the right to use and fresh working capital for investment is obtained. Finally, after analysis and assessment concludes, that leasing will optimize the financial management of the company Riego Nor SAC in the year 2014, which is described as sufficient in the conclusions and recommendations described in the final part of this research work.